THE EFFECT OF HDI AND POVERTY ON THE OPEN UNEMPLOYMENT RATE DURING THE PANDEMIC (CASE STUDY: SOUTH SULAWESI) - Irwandi, Irwandi; Marhawati, Marhawati; Andriani, Shadry; Abdur-Rabb, Ahmad faqhruddin; Adys, Himaya Praptani; Gani, Imam Prawiranegara (Universitas Negeri Gorontalo, 2024)
The phenomenon of the spread of covid-19 has a very deep impact on economic activity. south sulawesi province is one of the provinces whose economic growth is always above the national average also feels the impact of covid-19. HDI, poverty and unemployment are the variables that have the greatest impact. It is interesting to observe the economic variables of the South Sulawesi province during the Covid-19 period because it is one of the regions that has realistically high economic development every year. This study uses a cross-section of 24 districts/cities in South Sulawesi Province and a three-year time series 2020-2022 using secondary data obtained from the Central Bureau of Statistics. Fixed Effects Model in panel data analysis was used to analyze the data to observe the effect of HDI and poverty on the open unemployment rate. Based on the research findings, poverty has a negative and insignificant effect on open unemployment in South Sulawesi Province, while the human development index has a negative and significant effect on open unemployment.